CD8+ tumor infiltrating lymphocytes strongly correlate with molecular subtype and clinico-pathological characteristics in breast cancer patients from Sudan. Issue 1 (December 2016) - Mohamed, Mahmoud; Sarwath, Hina; Salih, Nada; Bansal, Devendra; Chandra, Prem; Husain, Nazik; Chouchane, Lotfi; Sultan, Ali; Bedri, Shahinaz
Abstract Background Breast Cancer in the Middle East and North Africa region (MENA) occurs in a younger age group of patients and is more aggressive than in Europe and North America. Little is known about the presence of immune infiltration and clinico-pathologic correlates in patients from the MENA region. Immune infiltration of most solid tumors carries a prognostic role. Adaptive immune cells and cytotoxic T-cells, in particular, play a positive prognostic role in patients undergoing treatment for breast cancer. Therefore, our preliminary study was aimed to identify and quantify the presence of tumor infiltrating lymphocytes (TILs) (CD8+, CD45RO+, and CD3+ ) in invasive breast cancer patients from Sudan. Additionally, TIL was correlated with patients' clinico-pathological characteristics. Methods Forty-three archival Formalin Fixed Paraffin Embedded samples of patients diagnosed with invasive breast cancer were collected at The Radiation and Isotope Centre in Khartoum, Sudan. CD8, CD45RO and CD3 immunostaining of FFPE tissue sections was performed. The mean percentage of lymphocytes in the invasive margin (stromal TILs) was scored. Results Overall distribution of CD3+, CD8+ and CD45RO+ in the tumor invasive margin were 100 %, 100 %, and 92.9 %, respectively. CD8+ TILs were significantly correlated with HER2/neu positive breast cancers and HER2/neu (+) tumors. Additionally, CD3+ TILs were significantly associated with lymph node metastasis. None of the other clinico-pathological variables had any significant association with CD3+ and CD45RO+ . Conclusions Our limited and preliminary study identified a strong correlation between CD8+ TILs and HER2/neu positive invasive breast cancers and HER2/neu (+) tumors.